ANALISA PENGARUH TEMPERATURE DAN SUDUT SCREW TERHADAP WAKTU EKSTRUSI PADA MESIN EKSTRUSI SINGLE SCREW DARI BAHAN RECYCLE HIGH DENSITY POLYETHYLENE (HDPE) - Hamidi, Ahmad Faresy; Putri, Fenoria; Arnoldi, Dwi (Politeknik Negeri Sriwijaya, Indonesia, 2022)
This research goal is to determine the effect of temperature and screw angle to extrusion speed with High Density Polyethylene as Material on Single Screw Extrusion Machine. On this research use 2 factor, first Temperature with 160°C, 170°C, and 180°C. and the second one is Screw Angle with 0°, 15°, 25°. The roller and puller are setted up to 16 Rpm, data from the research analyze with ANOVA method. And results from the data researcher got the fastest on Screw Angle 25° with 170°C Temperature. And the slowest on Screw Angle 0° with 160°C Temperature. The conclusion that researcher got is Temperature doesn’t effect on extrusion speed because it doesn’t significant, Whereas the Screw Angle have an effect on extrusion speed. Keywords : Extrusion Machine, Temperature, Screw Angle, ANOVA, Speed.